You can't take your body to a repair shop : a book about what makes you sick - Ziefert, Harriet; Ehrlich, Fred.; Haley, Amanda (Maplewood, N.J. : Blue Apple Books ; [San Francisco, Calif.] : Distributed in the U.S. by Chronicle Books, 2004)
Informs readers about the causes of such common childhood illnesses as stomachaches, colds, pimples, and allergies.
School Library Journal.
Science Books & Films (A.A.A.S.).
8.9
3-6
Keywords: Diseases -- Juvenile literature; Diseases; Diseases; Sick; Diseases